Accounting Data and Bank Future Failure: A Model for Indonesia - Abdul Mongid (The Indonesian Journal of Accounting Research, 2013)
Bank or Depository institution failures are widely perceived to have greater adverse effects on the economy and thus are considered more important than those of other types of business firms. In part, banks failures are viewed to be more damaging than other failures because of a fear that they may spread in domino fashion throughout the banking system. Thus, the failure of an individual bank introduces the possibility of system wide failures or systemic risk. This perception is widespread. It appears to exist in almost every country at almost every point in time regardless of the existing economic or political structure. As a result, bank failures have been and continue to be a major  public policy concern in all countries and a major reason that banks are regulated more rigorously than other firms.This research investigates and presents a model of bankruptcy prediction for the Indonesian banking system using accounting data. The study evaluates to what extent balance sheet (BS) and the off- balance sheet (OBS) items, as prescribed in the CAMEL (Capital Adequacy, Assets Quality, Management, Earning and Liquidity) ratings system,  can be used as an early warning of bank failure. The study also investigates what are really the most important determinants of bank failure. This research may provide the Indonesian Banking Supervision Agency  with a new tool that may help them in developing an early warning system for predicting future possible problems in the Indonesian banking system.